Pemberdayaan Remaja dalam Deteksi Status Gizi untuk mencegah Obesitas di Pondok Pesantren - Chandra, Filius; Jeki, Andicha Gustra; Fatmawati, Tina Yuli; Efni, Nel (Universitas Baiturrahim, 2025)
Nutritional status is a state of the body that is influenced by consumption, and eating habits. One of the most important factors in determining a person's health status is their nutritional status. Studies show that adolescents, especially in Islamic boarding schools, are at risk of experiencing nutritional problems due to unbalanced diets, lack of physical activity, and minimal awareness of the importance of monitoring nutritional status. In addition, the culture of eating together, lack of access to health information, and limited health facilities in Islamic boarding schools also worsen this situation. The lack of monitoring of adolescent nutritional status in the long term can have an impact on learning productivity, decreased immunity, and the risk of non-communicable diseases at an early age. The purpose of this Community Service is to empower adolescents at the Al Hidayah Islamic Boarding School in Jambi City to carry out early detection of nutritional status, so that obesity can be prevented. This activity was carried out at the Al Hidayah Islamic Boarding School, Jambi City. There were 13 community service participants, with the FGD method and guidance. The results of the community service were the formation of ORSADA Cadres, there was an increase in the knowledge of adolescent girls after being given health education about detecting nutritional status to prevent obesity. Cadres It is hoped that with ongoing mentoring, ORSADA cadres will be able to encourage the formation of a healthy lifestyle culture and improve the nutritional status of adolescents as a whole at the Al Hidayah Islamic Boarding School.